Pengaruh Capital Intensity, Leverage, Profitabilitas Dan Ukuran Perusahaan Terhadap Manajemen Pajak - Erma Wati; Hesty Ervianni Zulaecha; Hamdani Hamdani; Budi Rohmansyah (Amik Veteran Porwokerto, 2022)
The purpose of this study was to determine the effect of Capital Intensity, Leverage, Profitability and Company Size on Tax Management. Empirical Study of Consumer Goods Industrial Sector Companies Listed on the Indonesia Stock Exchange (IDX). The time period used in this study is 7 (five) years, starting from 2015-2021. The population in this study includes all consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the 2015-2021 period. The sampling technique used was the purposive sampling technique. Based on the predetermined criteria obtained 15 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX) website. The analytical method used is panel data regression analysis. The results show that firm size has a significant negative effect on tax management, capital intensity, leverage and profitability have no significant effect on tax management, and capital intensity, leverage, profitability and firm size together have an effect on tax management.